The Driver Role of Financial Development on the Economic Complexity: An Empirical Evidence from 33 BRI Participation Countries - Aslam, Aribah; Ghouse, Ghulam; Khan , Bismillah (Audit and Accounting Review, 2022)
Economic complexity plays a prominent role in the economic development of countries. So, economies need to improve their level of product sophistication. Several, researchers have mostly neglected the concept of economic complexity and its detrimental factors. Few economists have determined economic complexity with the help of socioeconomic determinants, while others have determined economic complexity through financial development index and institutions. This study employed the Generalize Method of Movement (GMM) to estimate the empirical inferences to cater the effects of endogeneity. Fiscal policy stances such as the log of final government consumption, GDP per capita income, institutions, and the lagged economic complexity have shown a positive and enormous impact on economic complexity. The findings of the current study have elucidated that the financial development index itself is negatively insignificant for economic complexity. However, after introducing the term ‘interaction’ with ‘institutions’, it reflected a positive and significant impact on economic complexity. So, as a policy measure, the selected sample BRI countries must regulate their finance system which would improve their institutional structure.